Pengaruh Upah, Angkatan Kerja, Indeks Pembangunan Manusia Terhadap Penyerapan Tenaga Kerja Jawa Barat - Solihah, Nabilatus; Arisetyawan, Kukuh (Universitas Negeri Surabaya, 2025)
Employment is the most fundamental problem because it covers social and economic aspects, especially in the province with the largest population in Indonesia, namely West Java. This research aims to review the influence of the minimum wage, labor force, and human development index on the level of labor absorption in 27 West Java regencies/cities from 2019 to 2023. This research uses quantitative research methods and panel data regression analysis techniques. The results of this research are that the labor force and human development index have a positive effect on labor absorption, and the minimum wage has a negative and significant impact. Simultaneously, these three independent variables influence labor absorption in West Java.